Pengaruh Penerapan SAK EMKM Terhadap Akses Pembiayaan Bagi UMKM Sarang Burung Walet Di Betung Kabupaten Banyuasin - Nandita, Nandita; Nafsiah, Siti Nurhayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study is motivated by the limited access to formal financing experienced by swallow’s nest MSMEs in Betung, Banyuasin Regency, which is largely caused by weak financial reporting practices. The purpose of this research is to analyze the effect of implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on financing access for MSMEs. The research employs a descriptive quantitative approach with a population of 60 swallow’s nest MSMEs in Betung, selected using purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination (R²) with the assistance of SPSS. The results show that the implementation of SAK EMKM has a positive and significant effect on financing access, as indicated by a t-value greater than the t-table and a significance level below 0.05. Thus, the better the implementation of SAK EMKM, the greater the opportunities for swallow’s nest MSMEs to obtain financing from formal financial institutions.